Achieving net-zero emission target in Africa : Are sustainable energy innovations and financialization crucial for environmental sustainability of sub-Saharan African state? - Musah, Mohammed; Onifade, Stephen Taiwo; Ankrah, Isaac; Gyamfi, Bright Akwasi; Amoako, George Kofi (Elsevier, 2024)
Following the rising importance of energy transition in the environmental sustainability discussion, it is imperative to understand the roles of sustainable energy innovations and financialization to reach informed inferences for policy formulation. We examined the environmental quality performance in Sub-Sahara Africa using the case of the resource-rich Ghanaian state vis-à-vis the possible moderating influence of green innovations and financial development. The empirical analysis encompassed various estimation issues, including structural breaks, heteroscedasticity, and normality in data structure. We simulated with the dynamic autoregressive-distributed lag technique and confirmed that financialization, resource rents, and economic growth are significant positive determinants of pollutant emissions. However, green innovations decrease the rate of pollution in the nation. Moreover, the interaction between green innovations and financial development improves ecological quality, while that between natural resources and financial development spurs pollution in the ecosystem. Furthermore, causal connections in the series indicated unidirectional causalities from green innovations, financialization, natural resource rents, and economic growth to pollutant emissions. However, the interactive terms between green innovations and financial development and between natural resource rents and financial development are bi-directionally related to ecological pollution. Hence, the study essentially suggests that the net-zero emission agenda of the Paris Accord is achievable from higher investments in green innovations while harnessing the benefits of international financial flows to boost the sustainability capacity of the Sub-Saharan Ghanian economy.
Keywords: Environment; Financial development; Green innovations; Resource rents; Ghana; fi=Taloustiede|en=Economics|